Effects of withdrawal from chronic escalating-dose binge cocaine on conditioned place preference to cocaine and striatal preproenkephalin mRNA in C57BL/6J mice - Zhang, Yong (2012)
Relapse is a serious problem for the effective treatment of cocaine addiction. RATIONALE: Examining cocaine re-exposure-induced behavioral and neurobiological alterations following chronic escalating-dose binge cocaine administration and withdrawal may provide insight into the neurobiological basis of cocaine relapse. OBJECTIVES: Our goal was to determine how exposure to chronic escalating-dose cocaine affects development of subsequent cocaine-induced conditioned place preference (CPP) and changes in endogenous opioid systems. METHODS: Mice were injected with either escalating-dose binge cocaine (15-30 mg/kg/injection × 3/day) or saline for 14 days and conditioned with 15 mg/kg of cocaine or saline (once per day for 10 days), starting either 1 or 14 days after the last day of binge injections. RESULTS: Mice exposed to chronic escalating cocaine did not develop CPP to cocaine when conditioning commenced on the first day of withdrawal (CPP test on day 10 of withdrawal). By contrast, mice did develop CPP to cocaine when conditioning started on the 14(th) day of withdrawal (CPP test on day 24 of withdrawal). Furthermore, preproenkephalin (Penk) mRNA levels in caudate putamen were significantly higher in mice that received 14-day withdrawal from escalating-dose binge cocaine before the CPP procedure (tested 24 days post-binge) than those that received 1-day withdrawal (tested 10 days post-binge). CONCLUSIONS: The rewarding effect of cocaine was blunted in early withdrawal from chronic escalating exposure, but recovered in more prolonged withdrawal. Time-dependent elevations in Penk mRNA levels may be part of the underlying mechanisms of this effect.